DETERMINATION OF EXPERTS COMPETENCE IN GROUP DECISION-MAKING - Kolpakova, Т. А. (Radio Electronics, Computer Science, Control, 2011)
The problem of taking into account the competence of experts in group decision-making is considered. The method for calculating the coefficient of confidence in the expert’s opinion in the survey using the analytic hierarchy is suggested.